2008
DOI: 10.1128/jcm.02335-07
|View full text |Cite
|
Sign up to set email alerts
|

Development of Multiplex PCR-Ligase Detection Reaction Assay for Detection of West Nile Virus

Abstract: We have developed a novel multiplex reverse transcription-PCR ligase detection reaction (RT-PCR/LDR) assayfor the detection of West Nile virus (WNV) in both clinical and mosquito pool samples. The method relies on the amplification of three different genomic regions, one in the coding sequence of nonstructural protein NS2a and two in nonstructural protein NS5, to minimize the risk of detection failure due to genetic variation. The sensitivity of the PCR is complemented by the high specificity of the LDR step, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…Any low-level polymerase errors remain unselected; thus, background noise is minimized. This method has been used in the detection of some viruses, oncogenes, and tumor-suppressor genes (Khanna et al, 1999;Rondini et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Any low-level polymerase errors remain unselected; thus, background noise is minimized. This method has been used in the detection of some viruses, oncogenes, and tumor-suppressor genes (Khanna et al, 1999;Rondini et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Any low-level polymerase errors remain unselected, and thus contribute only minimal background noise. It has been used in the detection of some viruses, oncogenes and tumor-suppressor genes (Khanna et al, 1999;Rondini et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Any low-level polymerase errors remain unselected, and so only contribute minimal background noise. PCR-LDR has been used in the detection of some viruses, oncogenes, and tumor-suppressor genes (Khanna et al, 1999;Rondini et al, 2008). The results showed that all of the egg production traits were significantly different between RW chickens and QY chickens, indicating that these 2 breeds might have different genetic backgrounds.…”
Section: Discussionmentioning
confidence: 99%